N-Acylthiqamide Metal Complexes- II N-Acetylthiobenzamide Complexes of Manganese (II), Iron (II), Cobalt (II), Nickel (II), Copper (II) and Zinc (II) Sulphates (Journal of Science and Technology, 2016)
The magnetic, electronic (reflectance) and infrared spectral properties of divalent metal complexes, [M(N-ATB)3] SO, and [Cu(N-ATB),]SO, (where M = Mn, Fe, Co, Ni and Zn; N-ATB = N-Acetylthiobenzamide are reported. Substitution of a methyl group in place of a phenyl one in N-Benzoylthiobenzsmide is found to weaken the C= 0 and C=S; and strengthen the N-H bonds of the metal chelate ring. Out of the two -n- - (C = 0 and C=S) transitions, the thiocarbonyl one shows stronger interaction in the metal complexes. The values of the magnetic moments are similar to those of analogous metal chelates.